Coupled on-site measurement/CFD based approach for high-resolution wind resource assessment over complex terrains. (1st June 2016) - Yan, B.W.; Li, Q.S.
Highlights: A coupled on-site measurement/CFD based approach is proposed. It can reproduce spatial variability of wind speed over complex terrains. A framework is presented for efficient and reliable wind resource assessment. A cross-validation study verifies the accuracy of the proposed method. The new method facilitates wind energy development in areas with complex terrains. Abstract: Wind resource assessment is essential for development of wind energy, particularly in the regions with complex terrains. This study proposes a coupled on-site measurement/CFD (Computational Fluid Dynamics) based approach to reproduce the spatial variability of wind speed for a region with complex terrain conditions. A complete framework is presented for wind resource assessment, which involves on-site measurement, CFD simulations and statistical analysis. Next, a case study on wind resource assessment for an offshore island with complex terrain features where is equipped with anemometers for long-term wind measurement is performed using the developed approach. The microscale effects in the assessment region are justified from CFD simulations with modified RNG k – ε model. A cross-validation of the numerical simulations against wind tunnel experimental results and on-site measurements indicates a good agreement. Consequently, a detailed wind resource map of the offshore island is attained through the wind data from a single measurement site combined with the CFD simulations, which is of great use for future wind farm siting and turbine micro-siting. The coupled on-site measurement/CFD based approach is expected to enable the efficient and reliable wind resource assessment and facilitate the wind energy development in the areas with complex terrain conditions.